2021
DOI: 10.1186/s13024-021-00465-0
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular protein components of amyloid plaques and their roles in Alzheimer’s disease pathology

Abstract: Alzheimer’s disease (AD) is pathologically defined by the presence of fibrillar amyloid β (Aβ) peptide in extracellular senile plaques and tau filaments in intracellular neurofibrillary tangles. Extensive research has focused on understanding the assembly mechanisms and neurotoxic effects of Aβ during the last decades but still we only have a brief understanding of the disease associated biological processes. This review highlights the many other constituents that, beside Aβ, are accumulated in the plaques, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(74 citation statements)
references
References 348 publications
(475 reference statements)
2
71
1
Order By: Relevance
“…This study, which is one of the first to directly screen for regulators of extracellular proteostasis, highlights new opportunities to understand the critical role for stress-responsive regulation of extracellular proteostasis in response to pathologic insults and paves the way for similar approaches to be applied for mapping the regulation of extracellular chaperoning networks in other models. While the conservation of the pathogen-stimulated increase in extracellular proteostasis capacity observed in worms remains to be established, mammalian homologs of many extracellular regulators identified in this study, including amyloid-like protein 2 (APLP2) and the brevican and neurocan core proteins, were found to be altered in mass spectrometric analysis of CSF from AD patients (Khoonsari et al, 2016;Gallotta et al, 2020), suggesting that these proteins could similarly influence extracellular proteostasis in the pathogenesis of AD and potentially other neurodegenerative diseases (Muller et al, 2017;Rahman and Lendel, 2021). However, this remains to be established.…”
Section: Discovering New Stress-responsive Mechanisms Involved In Reg...mentioning
confidence: 84%
“…This study, which is one of the first to directly screen for regulators of extracellular proteostasis, highlights new opportunities to understand the critical role for stress-responsive regulation of extracellular proteostasis in response to pathologic insults and paves the way for similar approaches to be applied for mapping the regulation of extracellular chaperoning networks in other models. While the conservation of the pathogen-stimulated increase in extracellular proteostasis capacity observed in worms remains to be established, mammalian homologs of many extracellular regulators identified in this study, including amyloid-like protein 2 (APLP2) and the brevican and neurocan core proteins, were found to be altered in mass spectrometric analysis of CSF from AD patients (Khoonsari et al, 2016;Gallotta et al, 2020), suggesting that these proteins could similarly influence extracellular proteostasis in the pathogenesis of AD and potentially other neurodegenerative diseases (Muller et al, 2017;Rahman and Lendel, 2021). However, this remains to be established.…”
Section: Discovering New Stress-responsive Mechanisms Involved In Reg...mentioning
confidence: 84%
“…The accumulation of Aβ is a long-term chronic process. When the balance between the production and elimination of Aβ is broken, the cognitive ability of patients with a large amount of Aβ accumulation will rapidly decline ( 47 , 48 ).…”
Section: Piezo1 Channel-mediated Chronic Inflammationmentioning
confidence: 99%
“…The aggregation of α-syn into Lewy bodies (LBs) and Aβ into amyloid plaques are associated with PD and AD, respectively. LBs containing α-syn are usually found as aggregated intracellular vesicles [ 175 ], while Aβ is deposited extracellularly as senile plaques [ 176 ]; however, several studies have shown overlapping symptoms between the patients with AD and PD, suggesting a cross-talk between the two proteins. A study in transgenic mice demonstrated that Aβ could augment the aggregation of α-syn [ 177 ].…”
Section: Cross-seeding Of Amyloid Proteins: Role and Mechanismmentioning
confidence: 99%